2014
DOI: 10.1080/02626667.2014.901515
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis for flood control operation of seasonal flood-limited water level incorporating inflow forecasting error

Abstract: The seasonal flood-limited water level (FLWL), which reflects the seasonal flood information, plays an important role in governing the trade-off between reservoir flood control and conservation. A risk analysis model for flood control operation of seasonal FLWL incorporating the inflow forecasting error was proposed and developed. The variable kernel estimation is implemented for deriving the inflow forecasting error density. The synthetic inflow incorporating forecasting error is simulated by Monte Carlo simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Rechecking characteristic flood levels has been studied by many relative scholars. Among them, Andrade [1], Li et al [2], and Zhou and Guo [3] had confirmed it. Currently, designing flood frequency and flood risk are usually used for quantitative analysis of rechecking characteristic flood levels.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Rechecking characteristic flood levels has been studied by many relative scholars. Among them, Andrade [1], Li et al [2], and Zhou and Guo [3] had confirmed it. Currently, designing flood frequency and flood risk are usually used for quantitative analysis of rechecking characteristic flood levels.…”
Section: Introductionmentioning
confidence: 74%
“…The characteristic parameter values of TGR are given in Table 1. The current flood control operating rule of TGR is referenced by Zhou and Guo [3]. Figure 2 shows that the mean and quartile of maximum flood levels increase with the increasing value of n, however, the upper of maximum flood levels is less than or equal to 180.4 m and the lower of maximum flood levels is larger than or equal to 175 m. Density probability curve of normal distribution for checking flood levels under four kinds of sample sizes is shown in Figure 3.…”
Section: Study Areamentioning
confidence: 99%
“…After several structural and non-structural measures are formulated and designed to cope with the breakout landslide, it is imperative to undertake a flood risk analysis [22][23][24][25] for selecting an appropriate and cost-effective emergency disposal solution from the standpoint of minimizing losses.…”
Section: Non-structural Measuresmentioning
confidence: 99%
“…The resistance can be determined by the safe water level H s . Thus, the flood control risk probability P R is defined as the probability of H ( t ) exceeding H s (Y. Zhou & Guo, ) PR=P()H()t>Hs. …”
Section: Flood Control Risk Analysismentioning
confidence: 99%